Path Analysis on the Factors Affecting Postnatal Depression - Widarti, Sri; Budihastuti, Uki Retno; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2019)
Background: Postpartum depression is one of the emotional disorders as a result of failure to accept the psychological adaptation process in women in the postpartum period. There are many factors of postpartum depression. This study aimd to determine factors affecting postpartum depression.Subjects and Method: This was a cross sectional study conducted at 30 villages, in Bantul, Yogyakarta, from February to March 2019. A sample of 210 postaprtum mothers was selected by purposive sampling. The dependent variable was the postpartum depression. The independent variables were age, education, income, ANC visit, number of children, parity, unwanted pregnancy, type of labor, family support, domestic violence, and stress. Postpartum depression was measured by Endinburgh postnatal depression scale. Psychological stress was measured by Kessler psychological distress scale. The other variables were collected by questionnaire. The data was analyzed by path analysis.Results: Postpartum depression was directly and positively affected by type of labor (b = 3.85; 95% CI= 0.16 to 7.54; p = 0.041), stress (b= 3.53; 95% CI= 0.34 to 6.72; p= 0.030), parity (b= 4.01; 95% CI= 0.04 to 7.98; p= 0.048), unwanted pregnancy (b= 9.43; 95% CI= 1.51 to 17.3; p= 0.019). It was directly and negatively affected by number of children (b = -5.05; 95% CI= -10 to -0.02; p = 0.049), family support (b= -3.73; 95% CI= -6.98 to -0.50; p= 0.024), and ANC visit (b = -8.18; 95% CI= -15.3 to -1.00; p= 0.026). Postpartum depression was indirectly affected by education, income, domestic violence, and age.Conclusion: Postpartum depression is directly and positively affected by type of labor, stress, parity, unwanted pregnancy. It is directly and negatively affected by number of children, family support, and ANC visit. Postpartum depression is indirectly affected by education, income, domestic violence, and age.Keywords: Postpartum depression, domestic violence, path analysisCorrespondence: Sri Widarti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: widacorset@gmail.com.Mobile: 082135814923.Journal of Maternal and Child Health (2019), 4(5): 358-368https://doi.org/10.26911/thejmch.2019.04.05.10